Efektivitas Konsumsi Buah Naga dan Fe terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil dengan Anemia - Mardiana Mardiana; Meldawati Meldawati; Nurul Hidayah (Pusat Riset dan Inovasi Nasional, 2023)
The government has carried out a TTD program but the prevalence of anemia still cannot be reduced. The red Dragon Fruit (Hylocereus polyrhizus) is effective for controlling iron deficiency and is almost entirely absorbable and helps increase iron absorption from food through the formation of ferrous ascorbate complexes. This study aims to determine the tendency of increasing hemoglobin (Hb) levels in anemic pregnant women before and after giving blood enhancer supplements and dragon fruit. This research method uses a quasy experiment research design. The population of this study is anemic pregnant women recorded in the Awayan Health Center area in December – January 2023. The final hemoglobin content of the intervention group was mostly not anemic amounted to 14 people (93.33%), while the hemoglobin content of the control group was mostly mild anemia amounted to 9 people (29.97%). Research shows that there is a significant increase in hemoglobin levels between before and after blood enhancer tablets and dragon fruit additives where p value = 0.000 and there is an effect of Hb levels after intervention from test results 1.1 times with a confidence level of 95%.